A Comprehensive Survey of Dynamic Data Mining Process in Knowledge Discovery from Database - Kumar, D. Ramana; Rao, S. Krishna Mohan (International Journal of Computer Sciences and Engineering, 2018)
Data mining and knowledge discovery in databases have been considered as an important research area in education and industry. This survey presents an overview, a description and future direction which denotes a standard for knowledge discovery using dynamic data mining process model. The paper mentions particular real-world applications, data mining techniques, challenges incorporated in real-world application of knowledge discovery, current and future research concepts in the field. The applications to both academic and industrial concerns are discussed. The major target of the survey is the integration of the research in this particular area and thereby assisting in improving the existing model by using dynamic data mining. The bonding between the knowledge discovery and dynamic data mining in real world is reviewed with appropriate examples. The survey critically evaluates the area of knowledge discovery database to inform users about various models and to develop various models using dynamic data mining. The knowledge discovery database management standards will help in promoting the industry growth and pushing the industry beyond the edge.